Electrical and optical properties of nanostructured copper (I) iodide (CuI) incorporated with ligand agent for dye sensitized solar cell applications (DSSC) - Ayib Rosdi, Zainun; Noor, U. M.; Rusop, M. (Academic Journals, 2011)
Dispersion of CuI solution incorporated with ligand or stabilizer in acetonitrile solvent has been deposited on glass substrates, where it formed a mixture of inorganic/organic thin film in order to study its characteristics for dye sensitized solar cell applications (DSSC). CuI thin film has been prepared by sol-gel process with incorporation of TMED as a ligand into the CuI solution. Particle size of the solution is measured after few hours of stirring. Then, the thin film was deposited by spin coating technique with appropriate parameters. The optical properties of the composite thin film have been examined to display the energy shifting, which support the improved band gap compared to that of the pure CuI film, while the electrical properties show improved conductivity of the hole conductor to be a function of the p-type semiconductor for DSSC. This result indicates that the electrical and optical properties of CuI film can be easily adjusted by the formation of composite film with proper ligand agents.